La política y el olvido: entre el crítico y el cineasta.Sobre Adiós a la memoria y Otro país. Muerte y transfiguración del nuevo cine argentino de Nicolás Prividera. - Enrique Schmukler (Cuadernos LIRICO)
This article concerning the work of Nicolás Prividera, both in terms of criticism and filmmaking, is based on the premise that the critic and the filmmaker operate in a complementary and simultaneous manner. This was evident in his first two documentaries, M (2007) and Tierra de los Padres (2011), which found their critical counterpart in the texts that the director published in specialized magazines and blogs, later compiled into his first book of critiques, El país del cine. Por una historia política del Nuevo Cine Argentino (2016). The same dynamic occurs with his latest feature film, Adiós a la memoria (2020), as well as Otro país. Muerte y transfiguración del nuevo cine argentino (2021). Thus, our objective is not so much to explore the roles of the critic and the filmmaker but rather to examine the dialogue established between criticism and documentary. In what ways do the questions posed by the critic find tentative responses within the work of the documentarian? As we embark on this journey to reflect on these interconnected aspects, the relationship between documentary, intimacy, and politics occupies a central position within our conclusions.